2003
DOI: 10.1001/archotol.129.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Sedation vs General Anesthesia for Pediatric Otolaryngology Procedures

Abstract: Various procedures can be performed safely, effectively, and with decreased hospital charges with the use of IVS administered by a pediatric sedation service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Findings are in line with a prior study reporting that IVCF placement was roughly $1000 more expensive per procedure for placement in the OR compared to placement in the FS, with most of the cost due to the presence of an anesthesiologist (15). Intravenous sedation is considerably less expensive than general anesthesia for many procedures (16)(17)(18)(19). Similarly, a recent report documented signifi cantly decreased cost but similar lower complication rates for chest Mediport placement by interventional radiology compared with surgery (20).…”
Section: Discussionsupporting
confidence: 84%
“…Findings are in line with a prior study reporting that IVCF placement was roughly $1000 more expensive per procedure for placement in the OR compared to placement in the FS, with most of the cost due to the presence of an anesthesiologist (15). Intravenous sedation is considerably less expensive than general anesthesia for many procedures (16)(17)(18)(19). Similarly, a recent report documented signifi cantly decreased cost but similar lower complication rates for chest Mediport placement by interventional radiology compared with surgery (20).…”
Section: Discussionsupporting
confidence: 84%
“…It has been suggested that upto 50% of all outpatient procedures could be performed with a Monitored anaesthesia technique(MAC) and the cost of perioperative care can be reduced upto 80% in comparison to general anaesthesia 1 Monitored Anaeshthesia care is the term used when an anaesthesiologist monitors a patient ,receiving local anaesthesia or administers supplemental drugs to patients undergoing diagnostic or therapeutic procedures. 2 The ASA defines MAC as instances in which an anaesthesiologist has been suggested to provide specific anaesthesia services to a particular patient undergoing a planned procedure in connection with which a patient receives local anaesthesia, or in some cases, no anaesthesia at all.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hypoxia (SpO 2 < 90%) varies considerably in the published literature [1.54% (2), 5.8% (8) and 16% (9)], as a result of differences in procedures, techniques, and definitions used for hypoxia. Transient oxygen desaturation is very common with the use of propofol for deep sedation, and the duration of desaturation cannot be assessed in a retrospective study unless it is routinely documented.…”
Section: Discussionmentioning
confidence: 99%